Social network analysis of psychological morbidity in an urban slum of Bangladesh: a cross-sectional study based on a community census - Rabbani, Atonu; Sarker, Malabika (BMJ open, 2018)
Objectives To test whether social ties play any roles in mitigating depression and anxiety, as well as in fostering mental health among young men living in a poor urban community. - Setting A cohort of all young men living in an urban slum in Dhaka, the capital of Bangladesh. - Participants All men aged 18-29 years (n=824) living in a low-income urban community at the time of the survey. - Primary and secondary outcome measures Unspecified psychological morbidity measured using the General Health Questionnaire, 12-item (GHQ-12), where lower scores suggest better mental status. - Results The GHQ scores (mean=9.2, SD=4.9) suggest a significant psychological morbidity among the respondents. However, each additional friend is associated with a 0.063 SD lower GHQ score (95% CI −0.106 to −0.021). Between centrality measuring the relative importance of the respondent within his social network is also associated with a 0.103 SD lower GHQ score (95% CI −0.155 to −0.051), as are other measures of social network ties. Among other factors, married respondents and recent migrants also report a better mental health status. - Conclusions Our results underscore the importance of social connection in providing a buffer against stress and anxiety through psychosocial support from one’s peers in a resource-constraint urban setting. Our findings also suggest incorporating a social network and community ties in designing mental health policies and interventions.
Gesehen am 18.05.2020